2021
DOI: 10.1021/acsnano.1c02538
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Color and Angular Appearance of Plasmonic Metasurfaces with Tailored Disorder

Abstract: The optical properties of plasmonic nanoparticle ensembles are determined not only by the particle shape and size but also by the nanoantenna arrangement. To investigate the influence of the spatial ordering on the far-field optical properties of nanoparticle ensembles, we introduce a disorder model that encompasses both "frozen-phonon" and correlated disorder. We present experimental as well as computational approaches to gain a better understanding of the impact of disorder. A designated Fourier microscopy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…By exploiting the light-matter interaction in the designed structures, the generated colors are superior to the traditional pigmentary colors in many ways, due to their large tunability, resistance to bleaching, and reduced dependence on toxic materials. Much recent research has demonstrated the use of ordered and disordered photonic structures to generate colors across the visible spectrum [7][8][9]. Periodically ordered photonic structures generate colors with the iridescent feature due to Bragg diffraction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…By exploiting the light-matter interaction in the designed structures, the generated colors are superior to the traditional pigmentary colors in many ways, due to their large tunability, resistance to bleaching, and reduced dependence on toxic materials. Much recent research has demonstrated the use of ordered and disordered photonic structures to generate colors across the visible spectrum [7][8][9]. Periodically ordered photonic structures generate colors with the iridescent feature due to Bragg diffraction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuniformity has recently emerged as a new framework to engineer light scattering and diffraction in a rational manner. Hyperuniform disordered (HUD) media are statistically isotropic and possess a constrained randomness such that density fluctuations on large scales behave more like those of ordered solids, rather than those of conventional amorphous materials. HUD patterns naturally arise in many physical systems, from the mass distribution in the early universe, structure of prime numbers, hydrodynamics, structure of amorphous ices, sheared sedimenting suspensions, to wave localization or colloidal packing . When translated into photonic materials, HUDs exhibit large and robust photonic band gaps as in photonic crystals, but are both complete and isotropic .…”
mentioning
confidence: 99%
“…As a result, HUDs display allowed modes that can propagate through the structure in an isotropic fashion as in random media. HUDs are a highly flexible platform to control light transport, emission, and absorption in unique ways, beyond the constraints imposed by conventional photonic architectures, , for the design of freeform waveguides, high-quality factor resonant defects and arbitrarily high-order power splitters, , hollow-core fibers, and photonic bandgap polarizers among others.…”
mentioning
confidence: 99%
“…[ 2 ] Especially, structural colors are under frequent investigation since they serve as a great inspiration for engineering of artificial coloration with numerous applications. [ 3–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[2] Especially, structural colors are under frequent investigation since they serve as a great inspiration for engineering of artificial coloration with numerous applications. [3][4][5][6][7] While the physics behind some chromatic structural colors is known for more than 300 years, [1] the generation of the brilliant whiteness of ultrathin structures such as the scales of the Figure 1a to perform ultrafast time-resolved light scattering spectromicroscopy on a single scale. [26,27] The observations are confirmed for disordered Bragg stacks (DBS) fabricated via direct laser writing (see Supporting Information) shown in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%